Media Coverage of Environmental and Social Change in Northern Norway’s Coastal Regions : Main Themes in National and International News - Kaltenborn, Bjørn Petter; Kaltenborn, Jenny F.; Baczynska, Barbara B.; Kornfeldt, Just; Hovelsrud, Grete K. (Arctic Institute of North America, 2021)
Media are important agents in the shaping of northern images. Media coverage influences public perceptions and policy governing resource and societal development. But popular media often provide incomplete and skewed representations compared to the documentation provided by scientific literature and the range of activities and interests present in a region. We conducted a topic analysis of media coverage of environmental and social change in the Helgeland, Lofoten, and Vesterålen regions in northern Norway and Svalbard in the high Arctic during approximately 2014 to 2018. Our findings show that popular media collectively contribute to an image of expanding economic development based on natural resource exploitation. However, this narrative is incomplete in terms of the societal dynamics linked to natural resource development as documented in the scientific literature and somewhat biased towards climate change, oil and gas exploitation, tourism, and marine harvesting. Emergency preparedness issues and economic transitions are under-communicated, and we conclude that the popular media narrative only partly represents an alternative to the government policy discourse on northern issues. northern Norway; media coverage; environmental and social change; Helgeland; Lofoten; Svalbard publishedVersion